Thai secondary school science classrooms: Constructivist learning environments - Puacharearn, Panomporn; Darrel, Fisher (2007)
This paper describes the first study conducted in Thailand (2002-2003) that resulted in changes in science teachers’ classroom environments. In the first phase of the study, the Constructivist Learning Environment Survey (CLES), an instrument for assessing students’ perceptions of the actual and preferred classroom environment through the constructivist perspective, was validated for use in Thailand. Second, typical Thai secondary school science classroom environments were described using quantitative and qualitative methods. Finally, the effectiveness of constructivist teaching in promoting improvement in classroom environments was evaluated through an action research process, involving the use of feedback on actual and preferred classroom environments. The sample consisted of seven secondary science teachers and their 17 classes of 606 students in Nakornsawan Province, Thailand. Student Actual and Preferred Forms of the CLES, assessing Personal Relevance, Uncertainty, Critical Voice, Shared Control and Student Negotiation, were administered. Factor analysis and internal consistency measures supported a five-factor structure for both actual and preferred forms. Students’ attitudes to science were also measured. The actual and preferred environments of different classes were described based on profiles of classroom environment scores. A number of teachers then participated in an attempt to improve their classroom environments, through the use of a constructivist teaching approach. Changes in classrooms did occur, thus supporting the effectiveness of constructivist teaching in improving learning environments and students’ attitudes towards science in Thailand.